Correlation Between Palatal Rugae Patterns and Digital Fingerprints in the Bengali Population: A Forensic Study - Dr. Rakshith Shetty; Dr. Surajit Bose; Dr. Jayanta Chattopadhyay; Dr. Subhalakshmi Sen; Dr. Maumita Bhattacharya; Dr. Pratistha Chhibber (The Bioscan, 2025)
Background: Human identification in forensic science is a critical process employed to establish the identity of individuals in criminal investigations, disaster victim identification, and legal proceedings. This process relies on a variety of scientific methods, including fingerprint analysis, DNA profiling, dental record evaluation, and facial recognition. Among these, fingerprint and DNA analysis are considered highly reliable due to their uniqueness and accuracy. Forensic anthropologists and odontologists also play a significant role by examining skeletal remains to determine age, sex, and ancestry. With advancements in technology, biometric identification and digital forensics have become integral in enhancing accuracy and efficiency. Aim: This study aims to evaluate the potential correlation between palatal rugae patterns and digital fingerprint types in individuals from the Bengali population. Materials and Methods: A total of 100 subjects (50 males and 50 females), aged 17–25 years, were recruited from Kusum Devi Sunderlal Dugar Jain Dental College and Hospital, Kolkata. Maxillary impressions were made using alginate, and the palatal rugae patterns were traced on dental stone casts. Only individuals without systemic diseases or prior orthodontic/prosthodontic treatment were included. Digital fingerprints were recorded using ink by rolling the thumb from the ulnar to radial side. Ethical clearance was obtained, and informed consent was secured from all participants.